Positive correlation between lipid accumulation product index and arterial stiffness in Chinese patients with type 2 diabetes - Mao, Jing; Gan, Shenglian; Zhou, Quan; Yu, Fang; Zhou, Haifeng; Lu, Huilin; Jin, Jing; Liu, Qin; Deng, Zhiming (Frontiers in Endocrinology, 2023)
Background: Many studies have confirmed that lipid accumulation products (LAP) predict arterial stiffness (AS) in hypertensive patients. But there is little research on the use of LAP in identifying early atherosclerosis in patients with type 2 diabetes mellitus (T2DM). The aim of this study was to determine the relationship between the LAP index and brachial-ankle pulse wave velocity (baPWV) in Chinese patients with T2DM.Methods: A total of 1471 Chinese participants with T2DM, ranging in age from 18 to 80, were included in this cross-sectional study. BaPWV measurements were used to calculate the AS. A baPWV greater than the 75th percentile (1700 cm/s) was defined as indicating increased AS. The LAP index was calculated from the combination of waist circumference (WC) and triglycerides (TG).Results: According to the quartiles of the LAP index, baPWV tended to increase after adjusting for sex and age. Multiple linear regression analysis showed that the beta coefficient (β) of baPWV increased by 31.0 cm/s for each unit of InLAP that was increased, and the 95% confidence interval (CI) was (6.5, 55.5) cm/s. In multivariate logistic regression analyses, after fully adjusting for confounders, the risk of elevated baPWV increased with each unit increase in InLAP, with an odds ratio (OR) of 1.3 (95% CI: 1.0, 1.8). According to the generalized additive model (GAM), we found that InLAP was positively correlated with baPWV and baPWV elevation. The results were the same for males and females. Subgroup analyses showed that the positive correlation between InLAP and elevated baPWV did not interact across all subgroups.In Chinese patients with T2DM, LAP was strongly and positively correlated with baPWV and elevated baPWV.